1979
DOI: 10.1002/bbpc.19790831008
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transfer from the Carbon Tetrachloride Radical Cation to Alkyl Chlorides, Alkanes, Alkenes and Aromatics

Abstract: Charge transfer from carbon tetrachloride radical cations to 17 solutes (alkyl chlorides, n‐ and c‐alkanes, alkenes and aromatics) was studied by pulse radiolysis. ‐ At gas‐phase ionization potential differences ΔI = (ICCl4 ‐ Is) smaller than 0.8 eV rate constants of the reaction up to two orders of magnitude lower than expected for a diffusion controlled reaction have been determined. The dependence of the rate constants on the ionization potential differences k vs. ΔI is explained in terms of a two‐step p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…This dissociation process should be well distinguished from the delayed transformation of the metastable ArOH + driven by a nucleophile such as Cl À formulated in eqn (8). The latter one happens on the late nanosecond scale.…”
Section: Energetics Of the Cation Dissociationmentioning
confidence: 96%
See 2 more Smart Citations
“…This dissociation process should be well distinguished from the delayed transformation of the metastable ArOH + driven by a nucleophile such as Cl À formulated in eqn (8). The latter one happens on the late nanosecond scale.…”
Section: Energetics Of the Cation Dissociationmentioning
confidence: 96%
“…In general, FET represents the bimolecular electron transfer from aromatic donor molecules to parent radical cations derived from non-polar solvents such as n-alkanes, 2,3 cycloalkanes [4][5][6] and alkyl chlorides. [7][8][9] These radical cations are usually generated by photolysis (1a) as well as radiolysis (1b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parent radical cations produced in the radiolysis of alkyl chlorides (here n -BuCl, reaction 1a) and alkanes are powerful oxidants that are able to generate a vast number of secondary radical cations . They ionize molecules having lower ionization potentials than theirs (IP ≈ 9.5−10.5 eV), and hence they appear to be universal tools for the generation of solute radical cations. Usually, this kind of one-electron oxidation is a diffusion-controlled reaction that is called free electron transfer (FET) (eq 1b) …”
Section: Introductionmentioning
confidence: 99%
“…Radiation-induced electron transfer in solutions offers a convenient way for producing radical cations (S .+ ) of a high variety of solute (donor or scavenger) molecules. As well studied for n -alkanes, cycloalkanes, and alkyl chlorides, such as butyl chlorides, dichloroethane, and carbon tetrachloride, in nonpolar solvents RX, the formed metastable parent ions react as a rule diffusion-controlled with solutes of lower ionization potential [reactions 1 and 2] It was recently found that using phenols (ArOH) or hetero analogous thiophenols and selenophenols as solutes, additionally to the expected radical cations (ArOH⎤ .+ ) in a comparable amount also heteroatom centered radicals (phenoxyls, ArO . )…”
Section: Introductionmentioning
confidence: 99%